2020
DOI: 10.15520/ijcrr.v11i05.805
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Online Shopping Experience on Risk P erception and Trust for Building 
Online Repurchase Intention

Abstract: Purpose: The purpose of this study is to determine the role of mediating risk perception and trust on the influence of online shopping experience on the intention to conduct online shopping transactions. Design/Methodology/approach: This type of research is quantitative, using preexisting measurement scales. Findings: The results of this study indicate that the experience of online shopping has no effect on risk perception, online shopping experience has a positive and significant effect on consumer confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In business-to-customer (B2C) e-commerce, trust has been scientifically demonstrated as one of the most important traits (Dash and Saji, 2008), and customer trust (CT) has become a much more influential component for e-services during the COVID-19 pandemic, as per Gunawardana and Fernando (2021), where e-service aspects affect consumer satisfaction and trust, and trust has a favorable effect on CS of e-groceries. CT and buying intentions are positively influenced by the OSE (Armilawati, 2020) and CS and retention are boosted by customers' favorable experiences (Tzeng et al, 2021). According to Rose et al (2011), the two most often reported outcomes of online consumer experience are satisfaction and repurchase intention.…”
Section: Online Shopping Experiencementioning
confidence: 99%
“…In business-to-customer (B2C) e-commerce, trust has been scientifically demonstrated as one of the most important traits (Dash and Saji, 2008), and customer trust (CT) has become a much more influential component for e-services during the COVID-19 pandemic, as per Gunawardana and Fernando (2021), where e-service aspects affect consumer satisfaction and trust, and trust has a favorable effect on CS of e-groceries. CT and buying intentions are positively influenced by the OSE (Armilawati, 2020) and CS and retention are boosted by customers' favorable experiences (Tzeng et al, 2021). According to Rose et al (2011), the two most often reported outcomes of online consumer experience are satisfaction and repurchase intention.…”
Section: Online Shopping Experiencementioning
confidence: 99%
“…Shopping experience (X2), (Armilawati et al, 2020) defines the shopping experience as a psychological condition in the form of a subjective response to purchasing products, both goods, and services, via the internet. The indicators used to measure consumers' online shopping experience are quoted from research by (Beenakker et al, 2010) in (Armilawati et al, 2020): online shopping experience, ability to use online shopping sites, convenience, and ease of use. 3.…”
Section: Figure 1 -Construction Of the Path Diagram 1) Research Type ...mentioning
confidence: 99%
“…Shopping Experience Variable (X2). The shopping experience is a psychological condition in the form of a subjective response to purchasing products, goods, and services (Armilawati et al, 2020). To support the shopping experience variable, in this study, four statement items were given to respondents, as in Table 2.…”
Section: 616mentioning
confidence: 99%